PENGARUH PEMBERIAN KACANG HIJAU TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL TRIMESTER III DI PUSKESMAS NAIONI - Nur Asyah Jamillah (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2019)
Indonesian is one country that has a high prevalence of anemia in pregnancy, which is around 40.1%. The cause of anemia is a condition where the amount of hemoglobin is less than normal. The need for pregnant women for increased iron is used for placental formation and red blood cells. The impact of iron deficiency during pregnancy can be at risk for the mother and fetus, bleeding during pregnancy and during labor, weakness and easily tired so that interfere with daily activities. In the fetus can cause Low Birth Weight. A person's hemoglobin level can be influenced by diet and nutrition. Green beans are one of the ingredients that contain substances needed for the formation of blood cells so that they can overcome the effect of decreasing hemoglobin levels. The purpose of this study was to determine the effect of giving green beans to increased hemoglobin levels in third trimester pregnant women in the Kupang Naioni Health Center in 2018 The research design used was pre-experimental research. The population in this study were all third trimester pregnant women at the Naioni Kupang health center, the sampling technique used was accidental sampling, with a total sample of 16 people. The research instrument used was the observation sheet. Measurements were made before and after being given green beans for 7 days with an observation sheet. The results of the study were then analyzed using Wilcoxon. Based on the Wilcoxon test, obtained Asymp. Sig. (2-tailed) or ρ is 0.005 <α (0.05), so H0 is rejected and H1 is accepted which means that there is an effect of giving green beans to an increase in hemoglobin levels in third trimester pregnant women. Keywords: Green Beans, Hemoglobin Levels